The Reliability of Tensiomyography for Assessment of Muscle Function in the Healthy Population: A Systematic Review. Issue 6 (29th December 2022) - Hanney, William J.; Kolber, Morey J.; Salamh, Paul A.; Moise, Stephon; Hampton, Daniel; Wilson, Abigail T.
ABSTRACT: Tensiomyography (TMG) is a noninvasive tool used to assess contractile tissue properties during an isometric muscle contraction. Owing to portability and versatility for assessing muscle parameters, TMG may be of value to the strength and conditioning (S&C) specialist. The purpose of this systematic review was to investigate the reliability of TMG measurements. PubMed, PEDro, MEDLINE, and Cochrane databases were searched up to September 2021 by 2 authors, who independently examined all titles and abstracts to determine initial eligibility. Inclusion criteria included any study assessing the reliability of TMG parameters, published in English, published in a peer-reviewed scientific journal, and included participants with no significant musculoskeletal conditions. Exclusion criteria included the following elements: TMG assessment process not clearly delineated, reliability of specific TMG parameters not clearly defined, and statistical methods for determining reliability not clearly defined. All studies underwent a quality assessment using the Modified Downs and Black checklist for assessing quality studies, and results were extracted from qualified articles. In total, 635 studies were identified, with 16 studies retained after full-text reviews. Twelve studies had poor quality, whereas 4 had fair quality. Noninvasive TMG has good to excellent absolute and interrater reliability for measuring the properties of skeletal muscles.